LANGUAGE CHOICE USED BY CHILDREN IN ACEHNESE FAMILY - Cut Intan lestari (Universitas Samudra, 2020)
This study deals with “language choice used by children in Acehnese family ”. The aims of this research is : ( 1 ) to find out what the language choice used by children in Acehnese family and ( 2 ) to find out what factors that influences language choice used by children in Acehnese family. This research used a descriptive qualitative method. The subject of This research is the children in Acehnese family. Aged, ( 9- 11 years ) 25children in this research, at Kapai Baro village, Darul Aman sub-district. From the results of the study this research do observations in four domains of language used ,(1) Family ,(2)Friendship,(3) Religion and (4) Education. This research findings three major factors that influence language choice used children in the Acehnese family , (1)educational, (2)social status, and (3)place. It was suggested by the researcher hope the reader understands and to another researcher, this research can be useful to be the literature on the same field.